Paradoxical Reactions to Biologicals in Chronic Inflammatory Systemic Diseases - Kremenevski, Igor; Sander, Oliver; Sticherling, Michael; Raithel, Martin; LastName, First Name Middle Name (Deutsches Ärzteblatt international, 2022)
BACKGROUND: Biological agents that contain substances affecting the immune system are increasingly being used to treat chronic inflammatory systemic diseases. Aside from the expected adverse effects, they can also induce unexpected paradoxical reactions (PR). A reaction is called paradoxical when a substance that is generally therapeutically effective induces the opposite of what is intended, with the new appearance or exacerbation of inflammatory changes in the skin and other organs. METHODS: The paradoxical reactions that have been described since 1997 are presented here on the basis of the available literature on the main types of chronic inflammatory systemic disease, which was retrieved by a selective search in the PubMed and Google Scholar databases. RESULTS: Many studies and registers to date contain no mention of paradoxical reactions. Anti-TNF-alpha treatment for patients with ankylosing spondylitis leads to paradoxical reactions in 19 per 1000 patient years, compared to 11 per 1000 patient years with conventional treatment; the corresponding frequency for paradoxical psoriasis in patients with other chronic inflammatory systemic diseases are 1.04-3.68 versus 1.45 per 1000 patient years. Paradoxical reactions tend to be more common with anti-TNF-alpha treatment than, for example, with the administration of ustekinumab, vedolizumab, and other agents. It is unclear whether some drugs have been noted to cause PR more commonly than others because of varying times since their approval, differences in immunogenicity, and differences between their target structures. CONCLUSION: Paradoxical reactions induced by biological agents are a problem confronting physicians in multiple specialties. They need to be distinguished from infectious and neoplastic diseases and from autoimmune conditions of other types. The treatment options for paradoxical reactions include local treatment, symptomatic therapy, prednisolone administration, and the discontinuation or switching of the biological agent, although some patients will react with a further paradoxical reaction to a different biological agent that is used instead.
CRIS-Team Scopus Importer:2022-04-29